Improving immunoassay detection accuracy of anti-SARS-CoV-2 antibodies through dual modality validation - Yuhao Ma; Daniel To; Jie Zeng; Lian C.T. Shoute; Meng Wu; Shawn Babiuk; Ran Zhuo; Carmen Charlton; Jamil N. Kanji; Lorne Babiuk; Jie Chen (Biosensors and Bioelectronics: X, 2022)
A novel test strategy is proposed with dual-modality detection techniques for COVID-19 antibody detection. The full-length S protein of SARS-CoV-2 was chemically immobilized on a glass surface to capture anti-SARS-CoV-2 IgG in patient serum and was detected through either Electrochemical Impedance Spectroscopy (EIS) or fluorescence imaging with labeled secondary antibodies. Gold nanoparticles conjugated with protein G were used as the probe and the bound GNP-G was detected through EIS measurements. Anti-human-IgG conjugated with the fluorescent tag Alexa Fluor 488 was used as the probe for fluorescence imaging. Clinical SARS-CoV-2 IgG positive serum and negative controls were used to validate both modalities. For fluorescence-based detection, a high sensitivity was noticed with a quantification range of 0.01–0.1 A.U.C. and a LOD of 0.004 A.U.C. This study demonstrates the possibility of utilizing different measurement techniques in conjunction for improved COVID-19 serology testing.